6(1 + 3x) = –6x – 18 The answers are No solution X=0 X=-1 X=-3 Question 6(1 + 3x) = –6x – 18 The answers are No solution X=0 X=-1 X=-3 in progress 0 Math Raelynn 1 month 2021-10-18T13:48:13+00:00 2021-10-18T13:48:13+00:00 1 Answer 0 views 0

## Answers ( )

Answer:x = -1Step by step:

6(1+3x)=−6x−18

Step 1: Simplify both sides of the equation.

6(1+3x)=−6x−18

(6)(1)+(6)(3x)=−6x+−18(Distribute)

6+18x=−6x+−18

18x+6=−6x−18

Step 2: Add 6x to both sides.

18x+6+6x=−6x−18+6x

24x+6=−18

Step 3: Subtract 6 from both sides.

24x+6−6=−18−6

24x=−24

Step 4: Divide both sides by 24.

24x

24

=

−24

24

x=−1